Power and influence under the prohibition of consecutive reelection: the case of the Chamber of Deputies of Mexico - Vazquez Ferrel, Carlos; Díaz Domínguez, Alejandro (Revista de Ciencia Política, 2020)
Party leaders seek candidates with the technical competence and career trajectories necessary to allow them to negotiate the legislative process, as well as to collaborate with the party leadership in relation to the coordination of both inter- and intra-party affairs. Using data from three legislative cycles of the Mexican Chamber of Deputies (2009 to 2016), we seek to explain the parliamentary actions of legislators in relation to characteristics such as their gender, mode of election, prior experience, and educational, legislative and partisan backgrounds. The objective is to identify some of the determinants of institutional power in a sui generis congress conditioned by the use of a mixed electoral system and a prohibition on consecutive re-election. The findings show that partisan leadership opportunities in the legislative branch tend to favor male legislators, those elected from party lists (as opposed to those elected by local majorities), those with previous legislative and partisan experience, and those whose political trajectories have seen them advance from the local to the national level.